Should Cash Transfers Be Confined to the Poor? Implications for Poverty and Inequality in Latin America - Pablo A. Acosta; Phillippe Leite; Jamele Rigolini (Institute for the Study of Labor (IZA), 2011)
This paper compares for 13 Latin American countries the poverty and inequality impacts of cash transfer programs that are given to all children and the elderly (that is, categorical transfers), to programs of equal budget that are confined to the poor within each population group (that is, poverty targeted transfers). The analysis finds that both the incidence of poverty and the depth of the poverty gap are important factors affecting the relative effectiveness of categorical versus poverty targeted transfers. The comparison of transfers to children and the elderly also supports the view that choosing carefully categories of beneficiaries is almost as important as targeting the poor for achieving a high poverty and inequality impact. Overall, the findings suggest that although in the Latin American context poverty targeting tends to deliver higher poverty impacts, there are circumstances under which categorical targeting confined to geographical regions (sometimes called geographic targeting) may be a valid option to consider. This is particularly the case in low-income countries with widespread pockets of poverty.
Keywords: D6; H5; O1; 330; cash transfers; targeting; social assistance; poverty; Öffentliche Sozialleistungen; Armutsbekämpfung; Wirkungsanalyse; Armut; Soziale Ungleichheit; Lateinamerika